HUBUNGAN STATUS BERAT BADAN LAHIR RENDAH DENGAN INSIDENSI PNEUMONIA PADA BALITA - Ardhea Eprily Pratiwi; Fransisca Chondro (Jurnal Akta Trimedika, 2025)
Pneumonia is an acute airway infection that often affects children, especially toddlers, with a significant mortality rate. One of the risk factors associated with pneumonia is low birth weight (LBW), which is a baby born weighing less than 2500 grams. However, the association between LBW and pneumonia in toddlers is still debated due to mixed research results. The purpose of this study was to analyze the association between LBW and pneumonia in children under five years old at Kembangan Hospital, West Jakarta. Cross-sectional study with secondary data from toddler medical records for the period January-October 2024. The sample amounted to 105 toddlers selected using consecutive non-random sampling method according to the inclusion and exclusion criteria. Data analysis using Fisher's exact test with a significance level of p < 0.05. The results of this study showed that there was no statistically significant association between LBW and pneumonia among under-fives (p=0.053). However, toddlers with LBW history experienced pneumonia (41.2%) at a higher rate compared to toddlers without LBW (18.2%). Other factors such as nutritional status and immunization may influence this result. Although no statistically significant association was found, the proportion of pneumonia was higher among under-fives with LBW. Further research is needed by considering other risk factors to strengthen the results.